2015
DOI: 10.5154/r.rchscfa.2014.08.032
|View full text |Cite
|
Sign up to set email alerts
|

Identificación del insecto agallador (Trioza rusellae Tuthill) en hojas de Brosimum alicastrum Swartz en Yucatán, México

Abstract: Gall (Trioza rusellae Tuthill) insect identification in AbstractT he insect Trioza rusellae Tuthill (Hemiptera-Triozidae) produces galls on the leaves of the Ramon (Brosimum alicastrum Swartz) tree, species with high nutritional value of the Peninsula of Yucatan. The insect was isolated and identified from collections in the municipalities of Muna and Sacalum, Yucatán. Five to 10 years old trees were sampled selecting branches with leaves showing galls. The samples were placed in plastic bags and taken to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Exploratory analyses carried out as part of our study showed that biomass, basal area, and stem density of deciduous species were higher on flat than on sloping sites (F ≥ 9.509, p ≤ 0.037). Flat sites provide more favorable conditions for vegetation development since they have deeper soils than sloping sites [62]. Besides the above, runoff and erosion take away water, mineral nutrients, and soil particles from sloping sites and deposit them on flat sites at the bottom.…”
Section: Influence Of Topography and Vegetation Structure On Litterfall Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exploratory analyses carried out as part of our study showed that biomass, basal area, and stem density of deciduous species were higher on flat than on sloping sites (F ≥ 9.509, p ≤ 0.037). Flat sites provide more favorable conditions for vegetation development since they have deeper soils than sloping sites [62]. Besides the above, runoff and erosion take away water, mineral nutrients, and soil particles from sloping sites and deposit them on flat sites at the bottom.…”
Section: Influence Of Topography and Vegetation Structure On Litterfall Productionmentioning
confidence: 99%
“…The geomorphology of the region consists of karstic limestone, with flat areas alternating with gently sloping hills (10-25%). Cambisol and luvisol soils predominate in flat areas, and leptosol soils on hills and sites with rocky outcrops [62]. Secondary vegetation of different ages since abandonment predominates in the region as a result of the long-standing use of slash-and-burn subsistence agriculture [63,64].…”
Section: Introductionmentioning
confidence: 99%
“…This raises two possibilities: (a) ruminants in the region have adapted to consuming this forage, even though it has a high calcium oxalate content, or (b) calcium oxalate could prevent herbivory from other organisms such as insects. Only one foliar insect pest (Trioza rusellae Tuthill, a psyllid that promotes the growth of gills in the leaves) for B. alicastrum in the state of Yucatan (Ascencio-Alvarez et al, 2015) has been reported to affect vegetative growth and consequently decrease photosynthetic rates (Cuevas-Reyes et al, 2004).…”
Section: Microbiological Analysesmentioning
confidence: 99%